2018
DOI: 10.1029/2018jb015943
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Properties of Nash Point Shale as a Function of Orientation to Bedding

Abstract: Understanding how fracture networks develop in shale formations is important when exploiting unconventional hydrocarbon reservoirs and analyzing the integrity of the seals of conventional and carbon capture and storage reservoirs. Despite this importance, experimentally derived fracture data for shale remains sparse. Here we characterize shale from Nash Point in South Wales, United Kingdom, in terms of ultrasonic wave velocities, tensile strength, and fracture toughness (KIc). We measure these properties in mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
47
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 40 publications
(88 reference statements)
13
47
1
Order By: Relevance
“…This particular (mature) shale was selected partly for its ability to be easily prepared and machined (Forbes Inskip et al, ; Text S1); a selection of samples were scanned and micro‐CT images taken before the hydraulic fracturing experiment to check for preexisting fractures within the sample (Figure SF1). The entire sample assembly is separated from the confining medium using an engineered nitrile jacket fitted with ports for 11 AE sensors evenly distributed over the sample (Figure c; Sammonds, ).…”
Section: Methods: a Laboratory Procedures For Microhydraulic Fracturingmentioning
confidence: 99%
“…This particular (mature) shale was selected partly for its ability to be easily prepared and machined (Forbes Inskip et al, ; Text S1); a selection of samples were scanned and micro‐CT images taken before the hydraulic fracturing experiment to check for preexisting fractures within the sample (Figure SF1). The entire sample assembly is separated from the confining medium using an engineered nitrile jacket fitted with ports for 11 AE sensors evenly distributed over the sample (Figure c; Sammonds, ).…”
Section: Methods: a Laboratory Procedures For Microhydraulic Fracturingmentioning
confidence: 99%
“…More recently, a number of groups have addressed fracture toughness measurement in shales, with studies by Lee et al (), Chandler et al (, ), Chen et al (), Kabir et al (), Luo et al (), and Forbes Inskip et al (). Lee et al () used semicircular bend specimens to measure fracture toughness in the Divider and Arrester orientations in the Marcellus shale, as well as at an angle of 30° to the Arrester orientation.…”
Section: Discussionmentioning
confidence: 99%
“…Various theoretical studies (e.g., Garagash, ; Zia et al, ) have demonstrated that K Ic becomes the dominant control on fracture propagation for conditions when the pressure gradient within a fracture has equilibrated, either due to a long timescale or a low fluid viscosity. Recent experimental studies of anisotropy and fracture deflection (Chandler et al, ; Forbes Inskip et al, ; Lee et al, ; Luo et al, ) tend to find strongly anisotropic K Ic values in the region of ≃0.2–1.5 MPa·m 12, with much lower K Ic values for fracture planes parallel to layering. This K Ic anisotropy is therefore thought to be a possible mechanism for the limitation of hydraulic fracture height (Zia et al, ).…”
Section: Introductionmentioning
confidence: 98%
“…Figure shows the tensile strength, σ T , of a wide range of rock types all plotted as a function of their mode‐I fracture toughness, K Ic . These data were compiled from Zhang (), Schmidt and Huddle (), Chandler et al (), Forbes Inskip et al (), and Chandler et al (). The relationship between σ T and K Ic should be independent of the method used to determine each parameter, provided the samples were of sufficient size in each case.…”
Section: Introductionmentioning
confidence: 99%
“…Tensile strength, σ T , as a function of mode‐I fracture toughness, K Ic , for a range of rock materials. The nonshale materials are from Zhang () and Chandler et al (), while the shale materials are from Schmidt and Huddle (), Chandler et al (), Forbes Inskip et al (), and Chandler et al (). The dashed and solid lines are least squares fits made to the nonshale and shale data sets, respectively (and forced to intercept the origin).…”
Section: Introductionmentioning
confidence: 99%